ASEAN Community 2015: Where Are We? - Raman Letchumanan (2015)
The ASEAN Leaders meeting in Kuala Lumpur this week will, among others, make the final assessment of the achievements over the last five years as they announce the realisation of the ASEAN Community by the end of the year. To what extent have the goals they set in 2009 been achieved?